Hubungan Antara Asupan Zat Gizi Makro dan Status Gizi dengan Kebugaran Jasmani Mahasiswa UKM Taekwondo - Intan Galih Cornia; Merryana Adriani (Amerta Nutrition, 2018)
Background: Taekwondo is a physical activity or body movement that is conducted repeatedly with muscles as the most active organ. The problems that occurs to the athletes is the poor-organized consumption pattern, thus they lack of nutritional intake. The good nutritional intake is obtained from the sufficient nutritional intake so that the physical fitness becomes better. Meanwhile, young adults require sufficient nutritional intake so that their physical fitness can be better.Objective: This research aimed to analyze the relationship between the nutritional intake and nutrition status with the physical fitness of the university students joining the student activity unit of taekwondo in Universitas Airlangga Surabaya.Methods: This research was the analytical research with the cross-sectional design. The sample of the research was as many as 52 people who were acquired by utilizing the simple random sampling. The data collection included nutritional status by measuring the weight and height to figure out the Body Mass Index (BMI) and 2x24 hours food recall to understand the food intake.Results: The result demonstrated that there was a relationship between the nutritional status (p=0.014) and the intake of energy, protein, carbohydrate, and fat (p=0.05) had no relationship with the physical fitness.Conclusions: It could that the nutritional status was related to the physical fitness. The respondents who had normal nutrition status obtained the good physical fitness. There should be the addition of information regarding the nutrients to obtain the good nutritional status.ABSTRAKLatar Belakang: Taekwondo merupakan aktivitas fisik atau gerakan anggota tubuh yang dilakukan secara berulang dan organ yang paling aktif yaitu otot. Permasalah yang sering terjadi pada olahragawan yaitu suka konsumsi makanan yang tidak teratur sehingga asupan gizinya kurang tercukupi. Asupan gizi yang baik diperoleh dari asupan gizi yang cukup sehingga kebugaran jasmaninya baik.Tujuan: Tujuan dari penelitian ini adalah menganalisis hubungan antara asupan zat gizi makro dan status gizi dengan kebugaran jasmani mahasiswa UKM taekwondo.Metode: Penelitian ini menggunakan desain studi cross sectional dengan jumlah sampel 52 orang, diambil secara acak sederhana menggunakan simple random sampling. Pengumpulan data meliputi status gizi dengan cara penimbangan berat dan pengukuran tinggi badan untuk mengetahui Indeks Massa Tubuh (IMT), food recall 2x24 untuk mengetahui asupan makannya dan tes balke untuk kebugaran jasmani. Analisis data yang digunakan dalam penelitian ini adalah analisis univariat dan bivariat dengan menggunakan kolerasi pearson.Hasil: Hasil penelitian menunjukkan terdapat hubungan antara status gizi (p=0,014) dengan kebugaran jasmani sedangkan asupan energi, protein, karbohidrat dan lemak (P=0,05) tidak terdapat hubungan dengan kebugaran jasmani.Kesimpulan: Status gizi berhubungan dengan kebugaran jasmani. Responden yang memiliki status gizi normal cenderung memiliki kebugaran jasmani yang baik. Perlu dilakukan penambahan informasi terkait zat gizi agar tercipta status gizi yang baik.